Use of Nuclear Magnetic Resonance-Based Metabolomics to Characterize the Biochemical Effects of Naphthalene on Various Organs of Tolerant Mice - Lin, Ching-Yu; Huang, Feng-Peng; Ling, Yee Soon; Liang, Hao-Jan; Lee, Sheng-Han; Hu, Mei-Yun; Tsao, Po-Nien (PLOS ONE, 2015)
Naphthalene, the most common polycyclic aromatic hydrocarbon, causes airway epithelium injury in mice. Repeated exposure of mice to naphthalene induces airway epithelia that are resistant to further injury. Previous studies revealed that alterations in bioactivation enzymes and increased levels of gamma-glutamylcysteine synthase in the bronchioles protect tolerant mice from naphthalene and its reactive metabolites. In our current study, tolerance was induced in male ICR mice using a total of 7 daily intraperitoneal injections of naphthalene (200 mg/kg). Both naphthalene-tolerant and non-tolerant mice were challenged with a dose of 300 mg/kg naphthalene on day 8 to investigate metabolite differences. The lungs, liver, and kidneys were collected for histopathology 24 h after the challenge dose. Bronchial alveolar lavage fluid (BALF) and both hydrophilic and hydrophobic extracts from each organ were analyzed using nuclear magnetic resonance (NMR)-based metabolomics. The histological results showed no observable injuries to the airway epithelium of naphthalene-tolerant mice when compared with the control. In contrast, airway injuries were observed in mice given a single challenge dose (injury mice). The metabolomics analysis revealed that the energy metabolism in the lungs of tolerant and injury mice was significantly perturbed. However, antioxidant metabolites, such as glutathione and succinate, were significantly increased in the lungs of tolerant mice, suggesting a role for these compounds in the protection of organs from naphthalene-induced electrophilic metabolites and free radicals. Damage to the airway cellular membrane, as shown by histopathological results and increased acetone in the BALF and perturbation of hydrophobic lung extracts, including cholesterol, phosphorylcholine-containing lipids, and fatty acyl chains, were observed in injury mice. Consistent with our histopathological results, fewer metabolic effects were observed in the liver and kidney of mice after naphthalene treatments. In conclusion, NMR-based metabolomics reveals possible mechanisms of naphthalene tolerance and naphthalene-induced toxicity in the respiratory system of mice.